Comparative study on individuals with and without alcohol dependence in terms of anger rumination - Vatansever, Merve; İlhan, İnci Özgür (Journal of Dependence, 2020)
Objective: The aim of this research is to compare the individuals with and without alcohol dependence in terms of anger rumination. Method: The total sample of study consists of 110 individuals. 55 of whom inpatient/outpatient who were diagnosed with alcohol dependence and 55 of whom without mental disorder diagnosis were matched with the patient group in terms of age, gender, and educational status. The socio-demographic information form constructed by the researchers, alcohol use history questions for the patient group, CAGE Questionnaire for comparison group, and Anger Rumination Scale (ARS) for both groups were applied. Results: There were no statistically significant differences between the two groups in terms of the total scores of ARS, Thoughts of Revenge, Understanding of Causes, Angry Afterthoughts, Angry Memories subscale scores. Among individuals with alcohol dependence, those who reported that they were in trouble with the law while having alcohol were found to be higher scores of Thoughts of Revenge, Angry Afterthoughts, total ARS than those who reported that they weren’t. Conclusion: This study findings indicate that anger rumination of individuals with alcohol dependence does not differ from those without alcohol dependence supports the relevant literature.